Eksplorasi Museum Gedung Sate Dengan Memanfaatkan Kanal Youtube Jurnalisa X Kisah Tanah Jawa Sebagai Sarana Pembelajaran IPS - Mushoddik Mushoddik; Lelly Qodariah Lelly Qodariah; Merina; Siwi Nur Rahmawati; Cahya Adhitya Pratama (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
The Gedung Sate Museum is one of the museums in the city of Bandung and is frequently visited by tourists. Digital development through Youtube is one of the media used for social studies learning, one of which is the Journalism Youtube account. This study used descriptive qualitative method. Data collection was carried out by watching videos and studying literature. The purpose of the research conducted by researchers was to analyze the Journalism Youtube channel by exploring the Gedung Sate Museum as a social studies learning tool. The results of the study explained that currently IPS learning is not only presented conventionally. Social studies learning trends have followed developments in the digital era by utilizing the existence of various social media. YouTube videos are a digital product that thrives on social media with various types of content. As a visual display, the video presents historical information which includes social studies in a short, concise and interesting way. This can be an effective social studies learning alternative in the digital era.